The going concern's accounting principle and its incorporation in corporate income tax law of Spain - Aldeia, Susana (2019)
The main goal of this paper is to understand how the going concern’s accounting principle was merged in the Spanish corporate income tax law. During this study the national tax law dispositions was analysed and an effort was made towards understanding what kind of tax figures or tax rules obey the investigated accounting principle in the studied jurisdiction. For this purpose, the spanish tax law was examined, particularly the - Ley del Impuesto sobre Sociedades. The results show that the going concern accounting principle was incorporated in the spanish accounting and tax laws, mainly because it assumes the accounting profit as a starting point to determine the taxable profit. Therefore, the accounting principles are incorporated, expressly or implicitly, in Spain's jurisdiction. It is possible to find the going concern accounting principle in several tax figures, such as the deduction of tax losses, the reinvestment and the capitalization reserve. The recognition or use of these fiscal figures by the company shows its determination in continuing to develop its activity. The case of the deduction of tax losses is one example because it makes sense that the company's taxable capacity can be determined under several tax periods and not an isolated period. Another is the case of reinvestment. When the legislator foresees an exemption, a reduction or a deferral of the tax bases in consequence of the reinvestment he deduces that this entity is fuctionig in continuity and will continue to operate in a predictable future.